Chlamydia trachomatis RNA in the environment: is there potential for false-positive nucleic acid amplification test results?. Issue 2 (30th October 2007) - Meader, E; Waters, J; Sillis, M
Abstract : Objectives: The ability of molecular methods to detect low levels of nucleic acid has led to the widespread application of techniques based on nucleic acid amplification tests in microbiological diagnosis. This exquisite sensitivity is recognised in the laboratory to require stringent precautions to avoid contamination, but this is not widely appreciated in clinical settings where samples are initially collected, and may be a particular problem in the non-clinical settings used for sampling as part of the National Chlamydia Screening Programme. There is thus the need to characterise the risk of false-positive results caused by environmental contamination in these areas. Methods: The extent of environmental contamination of Chlamydia trachomatis (CT) nucleic acid in clinical settings was investigated by swabbing surfaces within the vicinity of specimen collection. Laboratory experiments were designed to monitor the persistence of ribosomal RNA under simulated conditions and to investigate whether contamination of patients' specimens is a risk if environmental surfaces are contaminated. The Gen-Probe APTIMA Combo 2 system was used for CT rRNA detection. Results: CT rRNA was detected in swabs taken from examination rooms and toilet areas. Tests showed that this could persist for at least 50 days. The potential for clinical samples to become contaminated as a result of the presence of CT rRNA in the immediate environment was demonstrated in this simulated test. Conclusion: This study demonstrated that there is a risk of false-positive nucleic acid amplification test results, when samples are taken in an area that is contaminated with target nucleic acid.